MAKNA BEJADI KERONGGONT DAYAK KERABAT DI KABUPATEN SEKADAU - Herlina; Maria Fransisca (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to explain oral literature, specifically the meaning of the Bejadi Keronggont custom of the Dayak Kerabat tribe in Sekadau Regency. In this case, the author analyzes the meaning of the Bejadi Keronggont custom. The research method used is descriptive, with a qualitative research form. The research approach employed is the anthropological approach to literature. Based on the research, marriage in the custom of the Dayak Karabat Penyapat sub-tribe is not merely a legalization of the relationship between a man and a woman to produce offspring, but also the formation of a new family as a micro social institution accepted by society with equal rights and obligations. Marriage reflects the independence of the couple getting married by establishing a new household, symbolizing the unification of two families, as well as indicating the growth and sustainability of the community. The marriage process consists of four customary stages that must be undergone, namely ngantar cincin, batunang or berambeh, kawent, and bejadi, all of which reflect the journey towards a legitimate marriage in the custom.